Antifungal diterpene from Rhizome of wild bornean ginger, Hornstedtia havilandii (Zingiberaceae) - Rolinus Paulous; Zuraini Zakaria; Julianah Awang; Takashi Kamada; Charles S. Vairappan (Elsevier, 2022)
Hornstedtia havilandii (K. Schum.) belongs to the ginger (Zingiberaceae) family and is one of the nine reported species of Hornstedtia in Borneo. It is widely used as an important resource in traditional healing and cultural practices by the tribal communities. Rhizome of H. havilandii was extracted in ethanol and its biologically active antifungal metabolite was isolated via bioassay-guided separation technique. Isolated compound was subjected to spectroscopy measurements and the structure was elucidated as (E)-labda-8(17),12-diene-15,16-dial (1). Although 1 was identified as a previously published compound, we were able to differentiate and assign the chemical shift values for two overlapping carbons; C-4 and C-18 via Gaussian processing of the 13C-NMR data, and consequent 2D NMR assignments. The antifungal activities were seen against crustacean pathogenic fungal strains Lagenidium thermophilum, Haliphthoros sabahensis, and Haliphthoros milfordensis as MIC value of <82.78 μM (25 μg/mL) while Fusarium solani and Fusarium oxysporum required <165.56 μM (50 μg/mL). In addition, this is the first record of H. havilandii that produces labdane type diterpene. Data revealed here could be used as an important chemotaxonomic marker for this genus.